Indonesia's Role in Digital Diplomacy Through the Regional Conference on Digital Diplomacy (RCDD) - Pipit Listyowati, Christy Damayanti, Untari Narulita Madyar Dewi (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Developed countries and developing countries have now implemented digital diplomacy for the benefit of their foreign policy. Digital diplomacy is very important considering the massive development of technology. Indonesia as a developing country initiated the holding of the Regional Conference on Digital Diplomacy forum for 16 countries in the Asia-Pacific region. Where it is located regionally or regionally adjacent and has similar interests. In this study, researchers focused more on Indonesia's digital diplomacy through the Regional Conference on Digital Diplomacy. The author's analysis uses qualitative research methods by prioritizing literature studies or library research and is aligned with the theory of digital diplomacy and the theory of regionalism. The results of this study indicate that 1) Digital diplomacy is carried out by Indonesia to follow world digital technology; 2) Regional Conference on Digital Diplomacy is an effort made by the Ministry of Foreign Affairs of the Republic of Indonesia in building national forces through digital diplomacy meetings and the Asia Pacific region is a top priority in Indonesian regionalism politics; 3) Indonesian Digital Diplomacy through the Regional Conference on Digital Diplomacy is held as a follow-up to the International Seminar and International Conference on Digital Diplomacy. So that RCDD is in accordance with the objectives in the use of digital technology and increasing the contribution of Indonesia's foreign policy in the Asia-Pacific region.